2008
DOI: 10.1109/tmag.2008.2001318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot and Cold Rolling on Grain Size and Texture in Fe-2.4wt%Si Strips

Abstract: The magnetic properties of electrical steel such as magnetization behavior and specific magnetic losses are related to the microstructure and texture of the steel. The interest in the case of FeSi-alloys is to realize a low intensity on the 111 fiber, which is a different goal than that of conventional steels, where a high intensity on the 111 fiber and small grain size is desired. In this paper, we present and discuss some results of our recent studies on FeSi-alloys without phase transformation. The resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…The magnetic properties of electrical steels such as magnetization curves, permeability and specific losses are, to a large extent, correlated with the microstructure and crystallographic texture [1][2][3]. The resulting microstructural characteristics of materials are conditioned by the thermomechanical processing (TMP) [1][2][3][4][5][6][7] which involves a slab reheating, hot rolling, cold rolling and final recrystallization (RX) annealing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic properties of electrical steels such as magnetization curves, permeability and specific losses are, to a large extent, correlated with the microstructure and crystallographic texture [1][2][3]. The resulting microstructural characteristics of materials are conditioned by the thermomechanical processing (TMP) [1][2][3][4][5][6][7] which involves a slab reheating, hot rolling, cold rolling and final recrystallization (RX) annealing.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting microstructural characteristics of materials are conditioned by the thermomechanical processing (TMP) [1][2][3][4][5][6][7] which involves a slab reheating, hot rolling, cold rolling and final recrystallization (RX) annealing. Microstructure and texture evolutions during hot rolling depend on the rolling temperature and the coiling condition [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Their hot rolling parameters are summarized in Table 1. The evolution of the texture and microstructure during thermo-mechanical processing was discussed in detail elsewhere [13,14] Table 1: Summary of the hot rolling parameters for the different samples studied.…”
Section: Evolution Of Microstructure and Texture During Thermo-mechanmentioning
confidence: 99%
“…Therefore, no homogenisation of the microstructure during hot rolling takes place. Besides the specific technological rolling parameters, the existing gradients of strain and temperature affects much more the resulting microstructure and texture at the production of the hot strip compared to steels with a phase transformation [2][3][4]. It was found that higher intensities of θ-fibre can be obtained in the hot strip.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that higher intensities of the preferable θ-fibre texture of the hot strip result in a higher intensity after cold rolling. The results of previous studies indicate that there is an interaction between the microstructure and texture of the various processing steps: hot rolling, optional hot strip annealing, cold rolling and final annealing [3].…”
Section: Introductionmentioning
confidence: 99%